2021
DOI: 10.1186/s12889-021-11501-5
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and barriers associated with COVID-19 vaccination among the general population in Saudi Arabia

Abstract: Background Developing a vaccine against COVID-19 is considered a key strategy to end the pandemic. However, public acceptance is reliant on beliefs and perception toward the vaccine. Therefore, the study aimed to assess the beliefs and barriers associated with COVID-19 vaccination among the Saudi population. Methods An online self-administered questionnaire was distributed across the main regions of Saudi Arabia on May 2020. The questionnaire addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
100
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(149 citation statements)
references
References 29 publications
19
100
2
Order By: Relevance
“…Generally, the acceptance rate of COVID-19 vaccine in the Middle East is thought to be 23–66% [22] , [23] . In a study from Saudi Arabia, acceptance of the COVID-19 vaccine among the general population was less than 50% among 3101 participants [24] . An additional study showed that about 60% would take the COVID-19 vaccine [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the acceptance rate of COVID-19 vaccine in the Middle East is thought to be 23–66% [22] , [23] . In a study from Saudi Arabia, acceptance of the COVID-19 vaccine among the general population was less than 50% among 3101 participants [24] . An additional study showed that about 60% would take the COVID-19 vaccine [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for the study was calculated using WHO software for sample size determination in health studies. The sample size was measured using 44.7% prevalence of COVID-19 vaccination acceptance [6]. At 95% confidence level and 5% bound on error, the maximum calculated sample size was 380 participants.…”
Section: Sample Sizementioning
confidence: 99%
“…Similarly, a number of studies have been published from Saudi Arabia, which reported vaccine acceptance rates to range from 48% to 72% [5,6,[11][12][13]. The common barriers reported among the Saudi population include concerns about the safety and efficacy of vaccines, vaccines being a conspiracy, and a perceived low risk of COVID-19 infection [6,11,12]. Studies have also reported various factors associated with vaccine uptake which include fear of infection, level of trust of vaccines, level of trust in the health care system, age, gender, marital status, education, presence of chronic diseases, and previous influenza vaccine uptake [4,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations